2004
DOI: 10.1785/012003257
|View full text |Cite
|
Sign up to set email alerts
|

Faulting Induced by Forced Fluid Injection and Fluid Flow Forced by Faulting: An Interpretation of Hydraulic-Fracture Microseismicity, Carthage Cotton Valley Gas Field, Texas

Abstract: We analyzed precisely located microearthquake data detected during five hydraulic fracture treatments in the Carthage gas field of east Texas. The treatments were conducted in two adjacent boreholes within interbedded sands and shales of the Upper Cotton Valley formation. The microearthquakes were induced within narrow horizontal bands that correspond to the targeted sandstone layers. Events throughout all the treatments show strike-slip faulting occurring uniformly along vertical fractures trending close to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
215
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(227 citation statements)
references
References 59 publications
8
215
2
Order By: Relevance
“…In contrast, studies of hydrofracture-induced microearthquakes, especially in tight-gas environments, typically find b values of 2.0 and higher; indeed, Dinske (2009a, 2009b) report b of 2.50 for microearthquakes produced by hydrofracturing the Barnett shale. Second, the cumulative number and cumulative moment of microearthquakes induced by hydrofracture tends to increase linearly with the volume of fluid injected (e.g., Phillips et al, 2002;Rutledge et al, 2004;Shapiro and Dinske, 2009b), rather than occurring in bursts or clusters as is observed for DFW in Figures 4 and 13. Finally, the largest DFW earthquakes have similar magnitudes (M 3.3) to historical natural earthquakes in northeast Texas.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, studies of hydrofracture-induced microearthquakes, especially in tight-gas environments, typically find b values of 2.0 and higher; indeed, Dinske (2009a, 2009b) report b of 2.50 for microearthquakes produced by hydrofracturing the Barnett shale. Second, the cumulative number and cumulative moment of microearthquakes induced by hydrofracture tends to increase linearly with the volume of fluid injected (e.g., Phillips et al, 2002;Rutledge et al, 2004;Shapiro and Dinske, 2009b), rather than occurring in bursts or clusters as is observed for DFW in Figures 4 and 13. Finally, the largest DFW earthquakes have similar magnitudes (M 3.3) to historical natural earthquakes in northeast Texas.…”
Section: Discussionmentioning
confidence: 83%
“…At near isotropic stress conditions the fractures branch more strongly and without a preferred propagation direction, a phenomenom often referred to as high fracture complexity (e.g., Katsaga et al, 2015). During large-scale stimulations, there is a tendency for seismic clouds to develop perpendicular to the minimum principal stress direction σ 3 (Häring et al, 2008;Evans et al, 2005), particularly for HF operations (e.g., Rutledge et al, 2004), although for HS stimulations in crystalline rocks there are many examples in which the seismicity cloud is oblique to the σ 3 direction (e.g., Block et al, 2015;Murphy and Fehler, 1986;Pine and Batchelor, 1984), presumably reflecting the complex interplay between stress and the pre-existing fracture population that is suitably oriented for slip reactivation. Furthermore, individual seismicity clusters within the overall seismicity cloud often strike oblique to the maximum principal stress (Eaton and Caffagni, 2015;Deichmann et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…natural gas reservoirs (Rutledge and Phillips, 2003;Rutledge et al, 2004) and geothermal reservoirs (Moriya et al, 2002;Phillips, 2000). Eisner et al (2006) reported similar microseismic events that were monitored during hydraulic fracturing in oil and gas fields.…”
Section: Introductionmentioning
confidence: 67%